2017
DOI: 10.1111/jpn.12702
|View full text |Cite
|
Sign up to set email alerts
|

Safety of standardized Macleaya cordata extract in an eighty‐four‐day dietary study in dairy cows

Abstract: Summary The objective of this study was to evaluate the safety of a standardized Macleaya cordata Extract Product (MCEP) containing the quaternary benzophenanthridine alkaloids, sanguinarine and chelerythrine, when fed to dairy cows. Thirty‐six dairy cows were randomized into three groups with twelve cows/treatment in two replica pens for each treatment group: control (C) without MCEP added to feed, treatment 1 (SANG‐1000) with MCEP added to feed at 1,000 mg/animal/day (1.5 mg/kg bw/day) and treatment 2 (SANG‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 21 publications
0
5
0
3
Order By: Relevance
“…In another study, the inclusion of cinnamaldehyde and other additives in pig feeds decreased Salmonella Typhimurium faecal shedding and improved pig weight gain [29]. Furthermore, licorice and Macleaya cordata (Papaveraceae), which are phytogenic feed additives approved for livestock feeding in the European Union [30, 31] show that plant extracts have potential to replace antimicrobials in animal feed. Apart from their influence on animal performance, plant additives may also have a positive influence on environmental health by reducing noxious gas content in animal faeces and rumen gases thereby reducing the concentration and effects of greenhouse gases [32].…”
Section: Introductionmentioning
confidence: 99%
“…In another study, the inclusion of cinnamaldehyde and other additives in pig feeds decreased Salmonella Typhimurium faecal shedding and improved pig weight gain [29]. Furthermore, licorice and Macleaya cordata (Papaveraceae), which are phytogenic feed additives approved for livestock feeding in the European Union [30, 31] show that plant extracts have potential to replace antimicrobials in animal feed. Apart from their influence on animal performance, plant additives may also have a positive influence on environmental health by reducing noxious gas content in animal faeces and rumen gases thereby reducing the concentration and effects of greenhouse gases [32].…”
Section: Introductionmentioning
confidence: 99%
“…• Ingestão de alimento, produção e a composição do leite de vacas não foram afetados pelo extrato rico em sanguinarina e queleritrina 79 .…”
Section: Sanguinarina E Queleritrinaunclassified
“…De forma isolada, Wang et al 79 avaliaram um extrato vegetal rico em alcaloides de sanguinarina e queleritrina na dieta de vacas leiteiras, e não constataram variações na ingestão de alimento, na produção e na composição do leite. Além disso, os autores não detectaram resíduos de alcaloides de benzofenantridinas no leite das vacas.…”
Section: Sanguinarina Da Chelidonium Majusunclassified
See 1 more Smart Citation
“…They have a wide range of pharmacological activities, such as anti-inflammatory (Danielewski et al, 2022), anti-cancer (Zhu et al, 2020;Prabhu et al, 2021), antibacterial (Falchi et al, 2021;Lu et al, 2022), antifungal (Anjago et al, 2021), anthelmintic (Li et al, 2022), and immune enhancing (Liu et al, 2022a), etc. The biggest application of M. cordata is in livestock production, where studies have shown that MCE can provide a slight bitter taste in feed to increase animal intake (Chin, 2008;Wang et al, 2018). The main active ingredient of M. cordata, SAN, was included in the Chinese feed additive species list in 1999 (Ministry of Agriculture Announcement No.…”
Section: Introductionmentioning
confidence: 99%